Cost-effectiveness of telephone coaching for physically inactive ambulatory care hospital patients: economic evaluation alongside the Healthy4U randomised controlled trial. Issue 12 (10th December 2019) - Barrett, Stephen; Begg, Stephen; O'Halloran, Paul; Kingsley, Michael
Abstract : Objective: To assess whether telephone coaching is a cost-effective method for increasing physical activity and health-related quality of life for insufficiently active adults presenting to an ambulatory care clinic in a public hospital. Design: An economic evaluation was performed alongside a randomised controlled trial. Setting: Participants were recruited from an ambulatory care clinic in a public hospital in regional Australia. Participants: Seventy-two adults (aged 18–69) deemed insufficiently physically active via self-report. Interventions: Participants were randomised to either an intervention group that received an education session and eight sessions of telephone coaching over a 12-week period, or to a control group that received the education session only. The intervention used in the telephone coaching was integrated motivational interviewing and cognitive behavioural therapy. Outcome measures: The primary health outcome was change in moderate-to-vigorous physical activity (MVPA), objectively measured via accelerometry. The secondary outcome was the quality-adjusted life-year (QALY) determined by the 12-item Short Form Health Survey Questionnaire. Outcome data were measured at baseline, postintervention (3 months) and follow-up (6 months). Incremental cost-effectiveness ratios (ICERs) were calculated for each outcome. Non-parametric bootstrapping techniques and sensitivity analyses were performed to account for uncertainty. Results: The mean intervention cost was $279±$13 per person. At 6 months follow-up, relative to control, the intervention group undertook 18 more minutes of daily MVPA at an ICER of $15/min for each additional minute of MVPA. With regard to QALYs, the intervention yielded an ICER of $36 857 per QALY gained. Sensitivity analyses indicated that results were robust to varied assumptions. Conclusion: Telephone coaching was a low-cost strategy for increasing MVPA and QALYs in insufficiently physically active ambulatory care hospital patients. Additional research could explore the potential economic impact of the intervention from a broader healthcare perspective. Trial registration number: ANZCTR: ACTRN12616001331426.